Do Calcium and Potassium Levels Influence Ductal Patency in Preterm Infants? - Cakir, Ufuk; Tayman, Cuneyt; Buyuktiryaki, Mehmet; Unsal, Handan; Ozer Bekmez, Buse (American Journal of Perinatology, 2019)
Objective We investigated the relationship of serum potassium (K+) and ionized calcium (iCa2+) levels with the persistence of ductus arteriosus.Study Design This retrospective cohort study included infants with birth weight < 1,500 g and gestational age < 32 weeks. Serum K+ and iCa2+ levels at the 1st and 48th hour of life were measured from samples. The difference between the two levels was calculated for both serum K+ (ΔK+) and iCa2+ (ΔCa2+). These values were compared between hemodynamically significant patent ductus arteriosus (hsPDA) and non-hsPDA.Results Of 1,322 hospitalized preterm nonates, 1,196 were included in the study. Mean serum K+ levels at the 1st and 48th hour were higher and iCa2+ levels at the 1st and 48th hour were lower in hsPDA and non-hsPDA, respectively (p < 0.001). Ionized ΔCa2+ (–0.06 ± 0.13 vs. –0.02 ± 0.12 mmol/L) was higher in hsPDA (p < 0.001).Conclusion We demonstrated that serum K+ and iCa2+ level might play a role in ductal constriction.
Keywords: serum potassium; ionized calcium; patent ductus arteriosus; infants; premature; very low birth weight